Probiotic Potential of Lactobacillus Strains Isolated From Fermented Vegetables in Shaanxi, China - Liu, Chen; Xue, Wen-jiao; Ding, Hao; An, Chao; Ma, Sai-jian; Liu, Yao (Frontiers in Microbiology, 2022)
The objective of this study was to assess in vitro probiotic potential of Lactobacillus strains derived from artisanal fermented vegetables in Shaanxi, China. In total, 74 acid-producing Gram-positive strains with rod-shaped under the microscope were isolated from 16 samples of spontaneously fermented vegetables. Out of 74 strains, 26 showed high survival rate under low pH and high bile salts conditions and were subjected to molecular identification by 16S rRNA gene sequencing analysis. The results showed that 15 isolates belonged to Lactobacillus plantarum, 9 isolates belonged to Lactobacillus brevis, and the 2 remaining strains belonged to Weissella viridescens. The 24 Lactobacillus strains were investigated for their survival rate to transit simulated gastrointestinal tract, cell surface hydrophobicity, auto-aggregation, co-aggregation with pathogen, adhesion to Caco-2, antimicrobial activity, antibiotics susceptibility, radical scavenging ability, α-glucosidase inhibition, and the cholesterol assimilation. The results showed that the probiotic characteristics were strain-dependent, and several strains exhibited great probiotic potential with specific health benefits, which indicated that they might be excellent candidates for production of functional foods. Interestingly, it was first found that L. plantarum generally had higher antibacterial activities, α-glucosidase inhibition ability, and antibiotics susceptibility compared to L. brevis in this study. The results indicated that Lactobacillus strains isolated from fermented vegetables in Shaanxi, China, could be exploited as a promising novel probiotic source.